Binding of established antinuclear antibodies to neurons depends on tissue fixation and underlying autoantigens - Li, Lucie Y.; Höltje, Markus; Rasmussen, Helle Foverskov; Halle, Lennard; Mayrhofer, Marie; Blüthner, Martin; Prüss, Harald (Frontiers in Immunology, 2025)
Antinuclear antibodies (ANAs) are central biomarkers in rheumatological conditions and can drive disease pathology. Much less is known about the role of ANAs in neurological symptoms, although a number of experimental studies have demonstrated direct effects on neuronal function, for example in neuropsychiatric lupus erythematosus. Moreover, it is unclear whether the ANAs detected in HEp-2 cell-based assays, the gold standard for ANA diagnostics, can also be recognized in modern screening assays for anti-neuronal autoimmunity, such as staining on rodent brain sections or neuronal cultures. In this study, we therefore conducted a comparative mapping of ANA-positive sera with well-characterized HEp-2 patterns to central nervous system (CNS) tissue, utilizing fixed and unfixed murine brain sections and primary murine neurons. We screened 74 ANA-positive sera classified into 14 individual patterns and combinations thereof. Majority of the samples reacted with fixed primary neurons (99%, 73/74 sera), followed by fixed brain sections (93%, 69/74), but much less to unfixed mouse brain (54%, 40/74). While the PM/SCL- and RPOI-positive sera showed no binding to unfixed brain sections, the U1RNP (U1 nuclear ribonucleoprotein particle) and FBLN (fibrillarin) ANAs reacted strongly across all assays, indicating differences in antigen accessibility. These findings suggest that the majority of ANAs can interact with neural components, which may obscure the detection of other anti-neuronal autoantibodies. The foundational mapping of ANA binding in CNS tissue provided here can also facilitate recognition of “CNS-specific ANAs,” which bind to neuronal autoantigens but not to HEp-2 cells. Future studies should explore the association with certain neurological manifestations and the role of ANAs in neuronal pathology.